1825. Electronic Measure of Unnecessary Antimicrobial Use in US Veterans Affairs Medical Centers. (26th November 2018) - Jones, Makoto; Stevens, Vanessa; Jones, Barbara; Lewis, Julia; Peterson, Kelly; Madaras-Kelly, Karl; Graber, Christopher; Goetz, Matthew; Glassman, Peter
Abstract: Background: Antimicrobial inappropriateness is highly contextual and dynamic, depending not only on the patient's disease condition but also the information available at the time. To estimate the extent to which antimicrobials could theoretically be decreased with antimicrobial stewardship, we sought to capture unnecessary inpatient antimicrobial use in context over time as manifested in the electronic health record in Veterans Affairs (VA). Methods: We extracted antimicrobial use, administrative, admission, and laboratory data from all acute care VA medical centers between 2010 and 2016. Information present during Choice (hospital day [HD] 1–3), Change (HD 4–5), Completion (HD 6–7), and Post-completion (thereafter) was used to determine context. All antimicrobial use without any documented infection was considered unnecessary (admission, discharge, or otherwise). Choice Anti-MRSA agents were considered unnecessary in cellulitis without history of or current positive culture for MRSA. Choice HOMDR agents were unnecessary in cellulitis without history of positive culture for ceftriaxone-resistant Gram-negative rods. Also unnecessary were broad-spectrum antimicrobials (anti-methicillin-resistant Staphylococcus aureus [MRSA] and hospital-onset multidrug-resistant [HOMDR] organisms antimicrobials as defined by the National Healthcare Safety Network) administered without evidence of multidrug-resistant organisms existed during Change and Completion time frames. Results: Figure 1 demonstrates the distribution of facility proportions of unnecessary antimicrobials of different classes over time. Table 1 illustrates the percentage of unnecessary antimicrobials administered during choice, change, completion, and post-completion time-frames. Conclusion: By this measure, unnecessary anti-MRSA and HOMDR use has been decreasing in VA over time. The bulk of unnecessary use is empiric but there is a substantial proportion that is used for longer stays, during which time more information was likely present. More research is necessary to determine how well these simple rules correlate with clinical determinations of appropriateness. Also ICD-10-CM was implemented in October 2015, which may have introduced an ascertainment bias. Disclosures: V. Stevens, Pfizer, Inc.: Grant Investigator, Research grant.